Eksplorasi Etnomatematika pada Rumah Tradisional Pacenan - Dwi Putra, Eric; Fatma Lestari, Putri Dewi; Hidayatin, Nur (Universitas Islam Jember, 2025)
This research aims to identify the mathematical concepts found in traditional Pacenan houses. The methodology employed is ethnography with a descriptive approach. The research was conducted in Sumberbulus village, Ledok Ombo district, Jember regency, focusing on the Pacenan house as the subject. Data collection was carried out through observation, interviews, and documentation. The data analysis technique involved data reduction, data presentation, data analysis, and data exposition. The results of the study indicate that the traditional Pacenan house encompasses various geometric concepts, such as flat shapes (rectangles, triangles), solid shapes (cuboids), lines, angles, reflections (mirroring), congruence, and similarity. Elements of the house, such as the roof, doors, windows, and porch, reflect the application of geometric principles that have been passed down through generations within the Madurese culture. In conclusion, local culture can serve as a source of contextual mathematics learning through an ethnomathematics approach. Keywords: Ethnomathematics, Pacenan House